Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1471-2105-14-s19-s2
|View full text |Cite
|
Sign up to set email alerts
|

iVUN: interactive Visualization of Uncertain biochemical reaction Networks

Abstract: BackgroundMathematical models are nowadays widely used to describe biochemical reaction networks. One of the main reasons for this is that models facilitate the integration of a multitude of different data and data types using parameter estimation. Thereby, models allow for a holistic understanding of biological processes. However, due to measurement noise and the limited amount of data, uncertainties in the model parameters should be considered when conclusions are drawn from estimated model attributes, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Yet our analysis revealed large parameter uncertainties (Figure 6). As previous studies on small-scale models suggested that products or fractions of parameters often have lower parameter uncertainties, we computed equilibrium constants as a ratio of on and off rates of reversible reactions (Vehlow et al, 2013). We assessed the uncertainty of the equilibrium constants and their difference from 1.…”
Section: Mechanistic Model Unravels Molecular Mechanisms For Sensitivity and Resistance From Viability Measurementsmentioning
confidence: 99%
“…Yet our analysis revealed large parameter uncertainties (Figure 6). As previous studies on small-scale models suggested that products or fractions of parameters often have lower parameter uncertainties, we computed equilibrium constants as a ratio of on and off rates of reversible reactions (Vehlow et al, 2013). We assessed the uncertainty of the equilibrium constants and their difference from 1.…”
Section: Mechanistic Model Unravels Molecular Mechanisms For Sensitivity and Resistance From Viability Measurementsmentioning
confidence: 99%
“…Others : There are various further applications of dynamic graphs and their visualization. In research, for instance, in context of biology, evolving metabolic pathways [RUK*10], simulated chemical reaction networks [JSS*12] and uncertainties therein [VHK*13], or protein interaction networks [BFL12] are studied. Psychology and user interface research may profit from depicting eye gaze data as dynamic graphs recorded in eye‐tracking studies [BBR*14, HEF*13].…”
Section: Applicationmentioning
confidence: 99%
“…An open question is how to visualize a hierarchical structure that changes more significantly along with the dynamic graph. Additional data dimensions that have only been partly explored are dynamic multivariate graphs [BN11, YEL10, AAK*14], dynamic graphs with uncertainty information [VHK*13] and geo‐located graphs [HEF*13]. Finally, the effects of using continuous time with arbitrary fine sampling rates, rather than discretized time, are largely unexplored.…”
Section: Research Challengesmentioning
confidence: 99%
“…the outcomes of flux balance analysis can be shown by different thickness and color of corresponding reactions on the map, as in Escher [21]. Another example, the iVUN system (interactive Visualization of Uncertain biochemical reaction Networks) [22], uses the kinetic parameters encoded in the map directly via the visualization interface to run simulations. Finally, the recently upgraded COnstraint-Based Reconstruction and Analysis (COBRA) Toolbox [20] introduces a built-in visualization functionality for constraint-based modeling results and enables visualization of modeling results via the MINERVA platform.…”
Section: Milestones On the ‘Disease Maps Roadmap’mentioning
confidence: 99%